2018
DOI: 10.2147/opto.s164454
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment optical coherence tomography angiography to evaluate the peripheral fitting of scleral contact lenses

Abstract: PurposeThe aim of this study was to show the potential applicability of optical coherence tomography angiography (OCTA) for the evaluation of the peripheral fitting of fully scleral contact lenses.MethodsA pilot study was proposed fitting three different scleral contact lenses (Irregular Corneal Design [ICD]) with different sagittal heights (4200, 4800, and 5600 mm) in a healthy volunteer of 27 years old. We evaluated by means of optical coherence tomography (OCT, DRI Triton) the apical clearance achieved with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…To reduce ocular complications and discomfort anterior segment OCT imaging could be beneficial. 25 In addition, patient education is extremely important to prevent unwanted complications, even in patients with PK.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce ocular complications and discomfort anterior segment OCT imaging could be beneficial. 25 In addition, patient education is extremely important to prevent unwanted complications, even in patients with PK.…”
Section: Discussionmentioning
confidence: 99%
“…For a customized optimal adjustment, the lens has 4 differentiated zones that can be modified: central clearance zone (CCZ), peripheral corneal clearance zone (PCCZ), limbal clearance zone (LCZ) and scleral landing zone (SLZ) [ 16 ]. This SCL has been designed to be fitted mainly in irregular corneas [ 6 , 16 , 22 – 25 ]. The fitting was performed following the manufacturer guidelines: selection of the initial diagnostic lens according to the fitting table, insertion of the CL, evaluation of CCZ, assessment of central clearance, slit lamp examination of the SCL after 60 min of wearing and finally measurement of the over-refraction (ORx) to determine the final power of the CL [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Short-term changes in the bulbar conjunctiva and scleral tissue following SL wear have been identified with scleral topographers. 35 , 75 , 76 , 119 Gimenez-Sanchis et al 54 evaluated the peripheral SL fitting with AS-OCT angiography, which imaged limbal and conjunctival blood flow, and concluded that SL fitting could be optimized with the use of this technology.…”
Section: Measuring Scleral Lens Performancementioning
confidence: 99%